1998
DOI: 10.1159/000020849
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Measurement of Fetomaternal Hemorrhage following Diagnostic Cordocentesis

Abstract: Objective: The aim of this study was to investigate the effect of cordocentesis on fetomaternal hemorrhage (FMH). Methods: One hundred and three diagnostic cordocenteses, without any other associated procedure, were performed at 23–40 weeks’ gestation. FMH was detected using the Kleihauer-Betke staining of maternal blood taken immediately before and after cordocentesis. Results: Significant FMH occurred after 40 (38.8%) of the 103 procedures. An increased risk of fetal bleeding was associated with both an ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…With increasing age and decreasing BMD, relative movement between the lag screw and the femoral head has been described, which can lead to cut out of the lag screw particularly in cases of imperfect lag screw positions. 25,26 Although this poses a problem in elderly persons with hip fractures, lag screw cut out was not observed in our study and is typically not observed in younger individuals.…”
Section: Discussionmentioning
confidence: 50%
“…With increasing age and decreasing BMD, relative movement between the lag screw and the femoral head has been described, which can lead to cut out of the lag screw particularly in cases of imperfect lag screw positions. 25,26 Although this poses a problem in elderly persons with hip fractures, lag screw cut out was not observed in our study and is typically not observed in younger individuals.…”
Section: Discussionmentioning
confidence: 50%
“…Both methods were efficient in proving FMH in the second trimester. Chitrit et al . conducted a study involving 103 diagnoses for cordocentesis without any other associated procedures, at gestational ages of 23–40 weeks, and FMH was investigated using the Kleihauer–Betke test immediately before and after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…CVS is performed by removing a small sample of the placenta with either a catheter or a needle. For these reasons, both tests might be associated with an increased risk of FMH (4,(11)(12). The aim of our study was to explore if the quantification of fetal erythrocytes in maternal blood could be useful to control FMH as an adverse side effect of these tests to perform a prompt and appropriate management.…”
Section: Discussionmentioning
confidence: 99%